Family and community medicine in Peru: 30 years of specialization in persons, families and communities - Romero-Albino, Zoila (2019)
The specialty of family and community medicine turns 30 in Peru, this medical specialty is considered de effector primary health care and it is recognized as necessary for the achievement of better health outcomes, through the fulfillment of key attributes such as integrality, longitudinality, first contact and coordination. Family doctors are trained to provide comprehensive care and effectively respond to the majority of the population’s health needs at the first level of care; however, in Peru the public sector has not prioritized its insertion in the public workforce so far. This article describes the characteristics of a specialist in family and community medicine, the situation around them in Peru, it is also described how the group of family and community doctors could help to achieve a human, equitable and health system quality.